2018
DOI: 10.1093/nar/gky1230
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 degradation via G9a-mediated methylation promotes cell proliferation in colon cancer

Abstract: Posttranslational modifications of the Forkhead family transcription factor, FOXO1, have been known to have important regulatory implications in its diverse activities. Several types of modifications of FOXO1, including acetylation, phosphorylation, and ubiquitination, have been reported. However, lysine methylation of FOXO1 has not yet been identified. Here, we reported that FOXO1 is methylated by G9a at K273 residue in vitro and in vivo . Methylation of FOXO1 by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 54 publications
3
72
1
Order By: Relevance
“…Forkhead transcription factors are characterized by a winged helix DNA-binding domain and are essential for embryogenesis (Kaufmann and Knöchel, 1996). Some of them, such as FOXQ1, FOXQ3 and FOXO1, have been identified as regulating tumorigenesis and tumor progression (Mottok et al, 2018;Saito et al, 2016;Chae et al, 2019). It has been reported that the Forkhead box F2 transcription factor (FOXF2) functions as tumor suppressor in breast cancer, gastric cancer, colorectal cancer, lung cancer and hepatocellular carcinoma (Cai et al, 2015;Higashimori et al, 2018;Zhang et al, 2015;Kundu et al, 2016;Shi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Forkhead transcription factors are characterized by a winged helix DNA-binding domain and are essential for embryogenesis (Kaufmann and Knöchel, 1996). Some of them, such as FOXQ1, FOXQ3 and FOXO1, have been identified as regulating tumorigenesis and tumor progression (Mottok et al, 2018;Saito et al, 2016;Chae et al, 2019). It has been reported that the Forkhead box F2 transcription factor (FOXF2) functions as tumor suppressor in breast cancer, gastric cancer, colorectal cancer, lung cancer and hepatocellular carcinoma (Cai et al, 2015;Higashimori et al, 2018;Zhang et al, 2015;Kundu et al, 2016;Shi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…G9a functions as a histone methyltransferase (HMTase), modulating the methylation of histones H3K9 and H3K27 [7,8]. H3K9 methylation controlled by G9a is an essential process of transcriptional repression of many related genes during cancer development [9][10][11][12][13][14]. There has been an increasing amount of evidence regarding the role of G9a in tumorigenesis [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increasing amount of evidence regarding the role of G9a in tumorigenesis [15,16]. G9a is unregulated in various cancers, including human bladder [17,18], lung [19][20][21], colon [9,22] and breast cancer [14,[23][24][25][26], compared with normal tissue. G9a also contributes to the inhibition of E-cadherin expression in ovarian and endometrial cancer [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…FOXO1 as a tumor suppressor has been associated with multiple types of malignancies, including colon, cervical, prostate, gastric, and breast cancers (40, 44-47). Based on our findings that USP7 deubiquitinated H2BK120ub1 and recruited the PRC2 complex to suppress the transcription of FOXO1, we postulated that the USP7/EZH2-FOXO1 signaling pathway plays an important role in carcinogenesis.…”
Section: Resultsmentioning
confidence: 99%